A PHENOMENOLOGICAL READING OF EXISTENTIAL EXPRESSIONS IN YOUTH SOCIAL MEDIA POSTS: A LINGUISTIC AND CULTURAL INTERPRETATION - Ratna Sari Dewi; M. Manugeren; Efendi Barus (English Literature Department, Faculty of Economics, Law, and Humanities, 2026)
This study explores how young people articulate existential meaning through their social media posts, employing a qualitative phenomenological approach to interpret their lived emotional and cultural experiences. Focusing on linguistic patterns and thematic expressions, the research analyzes how adolescents express concerns related to identity, purpose, emotional disconnection, and resilience within digital spaces. A corpus of youth-generated posts from platforms such as Instagram, TikTok, and X was examined using thematic, linguistic, and phenomenological analysis. Findings reveal three major existential themes: purpose-seeking, loneliness and the paradox of digital visibility, and hope-driven self-reconstruction. Purpose-seeking expressions often employed progressive verb forms—such as “searching,” “trying,” and “figuring out” indicating an ongoing process of meaning-making rather than a fixed goal. Posts related to loneliness highlighted the tension between being seen and being understood, reflecting emotional vulnerability mediated by digital interaction. Meanwhile, affirmations of hope and resilience demonstrated future-oriented modal constructions that signaled efforts toward emotional recovery and agency. Culturally, the study shows that social media serves as a liminal space in which youth negotiate societal expectations, articulate vulnerabilities, and construct emerging identities. Overall, the findings suggest that existential expressions in youth digital communication are deeply shaped by linguistic choices and cultural environments, revealing social media as a critical site for understanding contemporary youth experiences.